2011
DOI: 10.4028/www.scientific.net/amr.305.378
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Electrochemical Properties of Foamed Ni-Mo Alloy by Pulse-Electrodeposition

Abstract: A variety of foamed Ni-Mo alloys coatings have been obtained using pulsed electrodeposition technique. The deposit is mainly composed of amorphous structural through the X-ray diffractions (XRD), the morphology clearly contains large amounts of multi-bubble pore structure with pentagonal or hexagonal skeleton structure and obviously stratifys through scanning electron microscopy (SEM) experimentals. This pentagonal or hexagonal skeleton structure and obvious stratification has a larger surface area. The electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…36 As such, when the grain size increases, the hardness also increases. In agreement with the above results, previous studies reported 17,18,20 that hardness is strongly inuenced by the molybdenum content. The enhancement in the hardness of Ni-Mo coatings with ultrasonic assistance is ascribed to the Mo content along with the much higher content the Mo in the coating and ner grain size.…”
Section: Hardness Of Coatingssupporting
confidence: 91%
See 1 more Smart Citation
“…36 As such, when the grain size increases, the hardness also increases. In agreement with the above results, previous studies reported 17,18,20 that hardness is strongly inuenced by the molybdenum content. The enhancement in the hardness of Ni-Mo coatings with ultrasonic assistance is ascribed to the Mo content along with the much higher content the Mo in the coating and ner grain size.…”
Section: Hardness Of Coatingssupporting
confidence: 91%
“…Some studies have reported that an increase in the Mo content of the coatings would cause the coating's structure to gradually transform from a crystalline phase to a nanocrystalline/ amorphous mixture. [19][20][21][22][23] When the Mo content increases up to 26 wt%, a two-phase structure with a mixture of nanocrystalline and amorphous phases arises, and the Ni-Mo alloys become quite amorphous/nanocrystalline when the content of Mo exceeds over 31 wt% to 35 wt%. 24 Thus, both Ni-Mo coatings with and without ultrasonication can be regarded as nanocrystalline phases.…”
Section: Composition Analysismentioning
confidence: 99%